2011
DOI: 10.1182/blood-2009-03-212803
|View full text |Cite
|
Sign up to set email alerts
|

Human and rhesus macaque hematopoietic stem cells cannot be purified based only on SLAM family markers

Abstract: Various combinations of antibodies directed to cell surface markers have been used to isolate human and rhesus macaque hematopoietic stem cells (HSCs). These protocols result in poor enrichment or require multiple complex steps. Recently, a simple phenotype for HSCs based on cell surface markers from the signaling lymphocyte activation molecule (SLAM) family of receptors has been reported in the mouse. We examined the possibility of using the SLAM IntroductionThe search for hematopoietic stem cell (HSC)-speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 26 publications
4
30
0
Order By: Relevance
“…Confirming a recent study (26), a minor subpopulation of CD34 ϩ HS/PCs expressing CD150 was detectable, which represent progenitor rather than stem cells. Wild-type MV infection of CD34 ϩ HS/PCs was inefficient, with little evidence of cell destruction.…”
Section: Transient Lymphopenia Is a Hallmark Of Measles Virus (Mv)supporting
confidence: 86%
See 1 more Smart Citation
“…Confirming a recent study (26), a minor subpopulation of CD34 ϩ HS/PCs expressing CD150 was detectable, which represent progenitor rather than stem cells. Wild-type MV infection of CD34 ϩ HS/PCs was inefficient, with little evidence of cell destruction.…”
Section: Transient Lymphopenia Is a Hallmark Of Measles Virus (Mv)supporting
confidence: 86%
“…SLAMF receptors are also involved in early phases of lineage commitment during hematopoiesis, and differential expression of CD150, CD48 (SLAMF2), and CD244 (SLAMF4) marks subsets of murine hematopoietic stem and progenitor cells (HS/PCs). This led to the term "SLAM code," whose applicability to human CD34 ϩ HS/PCs is as yet controversial (24,26,30,43,50).…”
Section: Transient Lymphopenia Is a Hallmark Of Measles Virus (Mv)mentioning
confidence: 99%
“…Of note, CD46 expression levels increased on cytokine-stimulated as compared with resting hCD34 1 cells, marked by a twofold increase in mean fluorescent intensity ( Figure 3A). In contrast, SLAM was almost undetectable at the surface of quiescent and stimulated hCD34 1 cells as reported, 31,33 which confirmed that SLAM, a valid surface marker for murine HSCs is not applicable for hHSCs ( Figure 3A and Larochelle et al 30 ). Nectin-4 was also not detected on HSCs.…”
Section: Of H/f-lv Binding To the Cd46 Receptorsupporting
confidence: 81%
“…28,29 This led to the term "SLAM code" whose applicability to human HSCs (hHSCs) and progenitors is still controversial. [28][29][30][31][32] Indeed, several reports already showed the absence of CD150 on the hCD34 …”
Section: Introductionmentioning
confidence: 99%
“…Although essential difference has not been observed between mouse and man regarding either the organs producing HSC or the transcription factors regulating their differentiation, completely different markers have been used to sort HSC in the two species. Human HSC do not express Sca1 or the SLAM family CD150 (Larochelle et al, 2011). While the CD34 + CD38 -phenotype has been regarded as the canonical marker set for human HSC, it has been repeatedly reported that murine adult HSC locate in the CD34 -CD38 + fraction (Randall et al, 1996;Matsuoka et al, 2001;Tajima et al, 2001).…”
Section: Difference Between Mouse and Manmentioning
confidence: 99%